Cloning and Characterization of TaSAP7-A, a Member of the Stress-Associated Protein Family in Common Wheat - Wenlu Li (Frontiers in Plant Science, 2021)
Stress association proteins (SAPs) are A20/AN1 zinc-finger domain proteins, which play important roles in plant adaptation to abiotic stress and plant development. The functions of SAPs in some plants were reported, but little is known about it in wheat (Triticum aestivum L.). In this study, we characterized a novel 2AN1-type stress association protein gene TaSAP7-A, which was mapped to chromosome 5A in wheat. Subcellular localization indicated that TaSAP7-A was distributed in the nucleus and cytoplasm. Unlike previously known A20/AN1-type SAP genes, TaSAP7-A was negatively regulated to abiotic stress tolerance. Overexpressing TaSAP7-A Arabidopsis lines were hypersensitive to ABA, osmotic and salt stress at germination stage and post-germination stage. Overexpression of TaSAP7-A Arabidopsis plants accelerated the detached leaves’ chlorophyll degradation. Association analysis of TaSAP7-A haplotypes and agronomic traits showed that Hap-5A-2 was significantly associated with higher chlorophyll content at jointing stage and grain-filling stage. These results jointly revealed that TaSAP7-A is related to the chlorophyll content in the leaves of Arabidopsis and wheat. Both in vivo and in vitro experiments demonstrated that TaSAP7-A interacted with TaS10B, which was the component of regulatory subunit in 26S proteasome. In general, TaSAP7-A was a regulator of chlorophyll content, and favorable haplotypes should be helpful for improving plant chlorophyll content and grain yield of wheat.